Periplasmic and extracellular production of cellulase from recombinant Escherichia coli cells. Issue 2 (19th May 2016) - Yıldırım, Zehra; Çelik, Eda
Abstract: BACKGROUND: Secretory production of recombinant enzymes in E. coli has significant advantages in bioprocess development, such as simplicity of purification, preventing proteolytic degradation, and providing greater access to substrates such as cellulose that opens the path to consolidated bioprocessing. RESULTS: In this study, an endoglucanase (Cel5A) from Fusarium graminearum was investigated for extracellular production in E. coli as a fusion to the YebF carrier protein, and compared with periplasmic production enabled by fusing the DsbA signal peptide to the N‐terminus of Cel5A. Yields of extracellular YebF‐Cel5A (175 mg L −1 ) were nearly 2‐fold higher than yields of periplasmic Cel5A. Periplasmic but not extracellular production of Cel5A increased ∼1.5‐fold following the addition of 0.4 mmol L −1 MgSO4 to the growth medium. While most of the divalent cations had an inhibitory effect on the periplasmic Cel5A activity, all cations tested enhanced the extracellular endoglucanase activity, with Co 2+ having the highest activation (4.3‐fold increase). Moreover, YebF‐Cel5A had 20% higher residual activity than Cel5A following 1 h heat treatment. CONCLUSION: The differences demonstrated for periplasmic and extracellular production of cellulases in E. coli provide the basis of bioprocess design parameters, paving the way to consolidated bioprocessing. © 2016 Society of Chemical Industry